Polypterus mokelembembe, a new species of bichir from the central Congo River basin (Actinopterygii: Cladistia: Polypteridae) - Schliewen, Ulrich K.; Schäfer, Frank (Zootaxa, 2006)
Polypterus mokelembembe sp. n. is described from the central Congo River basin. It is distinguished from all other Polypterus species except P. retropinnis, P. teugelsi and P. palmas palmas by its high predorsal scale count (32–37 vs. 11–28). It differs from P. teugelsi by having 57– 60 lateral line scales (vs. 63–65), from P. palmas palmas by a single large black blotch on the pectoral-fin base (vs. numerous small spots on the posterior part of the base), and from P. retropinnis by having a wider first dorsal-fin spine (6.4–8.1 vs. 4.6–6.1 % of HL), a smaller internostril distance (11.6–13.7 vs 14.3–18.0 % of HL), and fewer pectoral-fin rays (23–29 vs. 30– 34). Inasmuch as the type series (comprising three specimens) of Polypterus retropinnis Vaillant, 1899 is of mixed composition, and includes two specimens of P. mokelembembe, a lectotype is designated for P. retropinnis and a rediagnosis for that species is provided.